FAKTOR-FAKTOR YANG MEMPENGARUHI REMAJA DALAM PENGAMBILAN KEPUTUSAN MEMILIH STUDI LANJUT - Prayogi, Fiki; Irawati, Rosa (Jurnal Inspirasi Bimbingan dan Konseling (JGCI), 2020)
The selection of further studies at colleges both in location and study programs is a second career decision that must be considered by teenagers and parents. The first career decision has been made when teenagers will enter the high school education level, namely the selection of majors in Mathematics and Natural Sciences, Social Sciences or Language and Culture. This descriptive study aims to obtain an overview of the extent to which adolescent's need for career counseling services and the factors that influence adolescents in making further study decisions. The study was conducted by administering an online questionnaire. The results of the questionnaire attended by 662 adolescents aged 15-17 years found the need for career guidance and counseling services was at the top with a percentage of 46.07%. The questionnaire further revealed several main factors that were taken into consideration in choosing where to study further. Among them are quality (21.275%) followed by cost (14.65%) then location (6.95%). In addition, the survey results also revealed 94.3% chose to continue their studies in the city of residence and 5.97% chose to continue their studies outside the city / country where they lived